Pure Laparoscopic Hepatectomy Versus Open Hepatectomy for Hepatocellular Carcinoma in 110 Patients With Liver Cirrhosis: A Propensity Analysis at a Single Center. Issue 4 (October 2016) - Cheung, Tan To; Dai, Wing Chiu; Tsang, Simon H. Y.; Chan, Albert C. Y.; Chok, Kenneth S. H.; Chan, See Ching; Lo, Chung Mau
Abstract : Objective: To investigate the long-term outcomes of pure laparoscopic hepatectomy versus open hepatectomy for hepatocellular carcinoma (HCC) with background cirrhosis. Background: Laparoscopic hepatectomy has been gaining popularity, but has not been widely accepted, because published data were gathered from small numbers of patients. Methods: Data of patients diagnosed with HCC and cirrhosis treated by hepatectomy were reviewed. The outcomes of pure laparoscopic hepatectomy were compared with those of open hepatectomy. Propensity score matching of patients in a ratio of 1:3 was conducted. Results: There were 110 patients and 330 patients in the laparoscopic group and the open group, respectively. The laparoscopic group had less blood loss (150 vs 400 mL; P < 0.001), shorter operation time (185 vs 255 minutes; P < 0.001), and shorter hospital stay (4vs 7 days; P < 0.001). The median overall survival was 136 months in the laparoscopic group and 120 months in the open group. The 1, 3, and 5-year overall survival rates were 98.9%, 89.8%, and 83.7%, respectively, in the laparoscopic group, and 94%, 79.3%, and 67.4%, respectively, in the open group ( P = 0.033). The median disease-free survival was 66.37 months in the laparoscopic group and 52.4 months in the open group. The 1, 3, and 5-year disease-free survival rates were 87.7%, 65.8%, and 52.2%, respectively, in the laparoscopic group, and 75.2%, 56.3%, and 47.9%, respectively, in the open group ( P = 0.141). Conclusions: Pure laparoscopic hepatectomy for HCC can be carried out safely with favorable short-term and long-term outcomes even in cirrhotic patients at high-volume liver cancer centers.